A SLUG FLOW MODEL IN A LONG MILK TUBE FOR DESIGNING A MILKING UNIT CONTROL SYSTEM - A. Kupczyk; M. Gaworski; J. Szlachta; K. Tucki; J. Wojdalski; A. LuberaDski; B. Dró|d|and M. Krzywonos (Journal of Animal and Plant Sciences, 2019)
Automatic milking differs from natural sucking behavior, and it affects animal health. Subatmospheric pressure is the main parameter of a mechanical milker, and it is produced to overcome teat resistance, open the teat sphincter, keep the milking unit attached to teats, suck milk from the teat sinus and transport milk to the pipeline. Bernoulli’s equation was used to minimize the effect of inflowing air on the pressure drop between the milking cluster and the pipeline. A diagram for calculating the reduction in pressure was developed using the Goal Seek tool in MS Excel. A minimum pressure drop was noted at every milk flow rate when inflowing air had the required flow rate. In the proposed control system, the area of the air inlet was adjusted to minimize the pressure drop during milking. The developed model can be used to improve automatic control solutions in a milking unit.
Keywords: milking machine; automatic milking system; milk flow modeling; vacuum drop; flow rate